THE EFFECT OF SWEDISH MESSAGE THERAPY ON BLOOD PRESSURE IN PRIMARY HYPERTENSION PATIENTS - Eska Dwi Prajayanti; Irma Mustika Sari (P3M Universitas 'Aisyiyah Surakarta, 2022)
Background: Primary hypertension is one of the comorbidities in the transmission of the Sar-Cov virus. Relaxation therapy is needed in patients with hypertension in order to relax the blood vessels so that vasodilation will occur which causes blood pressure to return to normal. Swedish massage is a technique massage that focuses on relaxation and enhancing blood circulation by involving the muscles. Purpose: giving a swedish message as an effort to lower blood pressure in patients with primary hypertension. Methods: This study used in a research quasi-experimental design : one group pre test and post test design. The population in this study amounted to 8 respondents. Result: there is an influence between Swedish massage for lowering blood pressure in primary hypertension patient Conclusion: Swedish massage that is carried out regularly and consistently can be used to lower blood pressure in patients with primary hypertension